BENTUK-BENTUK STRATEGI AMBUSH MARKETING YANG DIJALANKAN OLEH PIHAK SPONSOR PADA KEJUARAAN DJARUM INDONESIA OPEN - Ygnasius Dio Nanda Permai (Universitas Katolik Widya Karya Malang, 2019)
The role of sport sponsorship as the main option in the marketingcommunication has become a very vital part in funding various kindactivities such as sports, music, soni cultural and social activities.Ambush marketing related to sport, where a company which is notan official sponsor of the event (official partner) conduct a businessthat includes their names, products, and services to a sporting eventor kopetisi with a marketing strategy that is